2006
DOI: 10.1051/0004-6361:20053137
|View full text |Cite
|
Sign up to set email alerts
|

A catalogue of eclipsing variables

Abstract: A new catalogue of 6330 eclipsing variable stars is presented. The catalogue was developed from the General Catalogue of Variable Stars (GCVS) and its textual remarks by including recently published information about classification of 843 systems and making corresponding corrections of GCVS data. The catalogue 1 represents the largest list of eclipsing binaries classified from observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(118 citation statements)
references
References 37 publications
4
107
0
Order By: Relevance
“…In addition to querying for any existing RV values, we also queried for multiplicity flags from catalogues using VizieR (Dommanget & Nys 2002;Malkov et al 2006;Pourbaix et al 2004;Worley & Douglass 1996), whether the system has previously been identified to have one or more companions. Out of our sub-sample of the overall SACY sample and probing only the SB systems, we found the previous multiplicity results:…”
Section: B2 Archival Multiplicity Flagsmentioning
confidence: 99%
“…In addition to querying for any existing RV values, we also queried for multiplicity flags from catalogues using VizieR (Dommanget & Nys 2002;Malkov et al 2006;Pourbaix et al 2004;Worley & Douglass 1996), whether the system has previously been identified to have one or more companions. Out of our sub-sample of the overall SACY sample and probing only the SB systems, we found the previous multiplicity results:…”
Section: B2 Archival Multiplicity Flagsmentioning
confidence: 99%
“…There has been a very large amount of effort invested in the search and characterization of eclipsing binaries in different evolutionary stages (Popper 1980;Strassmeier et al 1993Barrado et al 1994Malkov et al 2006). Recently a significant number of both low-mass and PMS EB have been incorporated into this essential database (Shkolnik et al 2008;Stassun et al 2014;David et al 2016).…”
Section: Sizes: Eclipsing Binariesmentioning
confidence: 99%
“…Among the four previously-known sources from Table 2, three (KSP-V871, V977, V1099) are classified as eclipsing binaries (Christiansen et al 2008;Malkov et al 2006) while the other one (KSP-V981) is an AGN (Jones et al 2009). This shows that our classification is overall in a good agreement with previous results.…”
Section: Classifications and Variable Typesmentioning
confidence: 99%
“…In other words, while Malkov et al (2006) This list includes 18 objects in total, with 14 from Table 1 and 4 from Table 2; their object id. in this paper is listed in column (1), their name as appearing on SIMBAD is shown in column (2), and their primary reference is listed in column (3).…”
Section: Classifications and Variable Typesmentioning
confidence: 99%